Natural Radioisotopes Determination in Groundwater and Tap Water using Gamma Spectrometry - Trabidou, G.; Florou, H.; Angelopoulos, A.; Sakelliou, L. (HNPS Advances in Nuclear Physics, 2019)
Samples of underground drinking water -tap water, water from drilled wells and springs- have been collected from selected sites in Ikaria island. Concentration levels of 226Ra, 228Ra and 222Rn have been analysed by gamma spectrometry. The effective dose equivalents from ingestion of water are in the range 0.1-114μSv.y-1 for 222Rn and 25-175 μSν-1 for 226Ra. The respective range from inhalation of 2 2 2Kn released from water is 0.36-85 μSν.y-1.